PENGABDIAN KEPADA MASYARAKAT: PELATIHAN MENJADI PEMBAWA ACARA DENGAN NASYIATUL AISYIYAH KOTA PADANGSIDIMPUAN TAHUN 2024 - Khatib Lubis; Ainun Jariyah (CV. Alfa Pustaka, 2024)
The training as a host for members of Nasyiatul Aisyiyah Padangsidimpuan City aims to improve communication skills and public speaking skills. The host or MC (Master of Ceremony) requires special skills in communicating, conveying information, and managing the course of the event with confidence. The training method used in this activity is a participatory and practice-based approach, where participants are directly involved in each training session. The results of the training showed that 85% of the participants experienced a significant improvement in public speaking skills, event management, and increased confidence. This training makes a positive contribution to the empowerment of Nasyiatul Aisyiyah members in carrying out organizational activities and communicating with the community.